Studi Analisis Penilaian Kemampuan Berpikir Tingkat Tinggi Level I Tahap Decision Making Menggunakan Model Poe Berbasis Inkuiri-Humanistik pada Praktikum Fisika Dasar - Umi Pratiwi; Nurhidayati Nurhidayati (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2017)
High-level thinking skills are an important capability as part of the problem-solving process. This study aims to determine the ability of high-level thinking at the level I decision-making phase before the initial problem-solving stage, namely the large size of the influence of the application of the model POE Inquiri-Humanstic (variable x) to the ability of thinking high level level I at the decision-making stage (variable II) . This study uses the application of inquiry-humanistic POE model as a solution in solving the problems that are being developed by physics education students. The subjects of the study used one group of subjects without any comparison, ie the second semester students of physics education courses in the Physics Basic lab course. The research data is done by using observation and high level thinking test (pretest / early test / post test). The research results show the application model of inquiri-humanistic POE reproduction of 10.2% on the ability of high-level thinking level I at the decision-making stage. It is expected that the next level level can be measured significantly with the implementation of inquiri-humanistic POE model.